Effectiveness of a Self-Esteem Enhancement Intervention Integrated into Standard CBT Protocol for Improving Quality of Life in Patients with Colorectal Cancer - Lavinia Alina Rat; Timea Claudia Ghitea; Adrian Marius Maghiar (European Journal of Investigation in Health, Psychology and Education)
Cognitive behavioral therapy (CBT) has proven effective in addressing the psychological and emotional challenges of cancer. This study evaluated the impact of a self-esteem enhancement intervention integrated into a standard CBT protocol on the quality of life and self-esteem of women with colorectal cancer. Conducted at Spitalul Județean Clinic Bihor (Romania) between August 2020 and March 2024, the study included 67 women aged 32 to 66 years undergoing chemotherapy or combined chemotherapy and radiotherapy. This study aimed to evaluate the impact of a self-esteem enhancement intervention integrated into a standard CBT protocol on the quality of life and self-esteem of women with colorectal cancer. Participants were assigned to a CBT group, receiving eight weekly sessions based on the Simonton Program, or a control group on a psychotherapy waiting list. Quality of life was assessed using the EORTC QLQ-C30 questionnaire, and self-esteem was measured through actual and ideal self-perceptions. A repeated measures ANOVA analyzed changes in both outcomes. Results showed a significant improvement in quality of life (F = 6.33, df = 1, 65, p < 0.05) and self-esteem (F = 4.46, df = 1, 65, p < 0.05) in the CBT group, whereas no improvements were observed in the control group. Self-esteem was enhanced through reduced discrepancies between actual and ideal self-perceptions, especially in cognitive and emotional dimensions. Physical functioning improved but was less pronounced, influenced by disease progression and treatment stage. No significant changes were observed in social functioning, suggesting that longer-term interventions may be needed. These findings highlight CBT as a valuable complementary intervention in oncology care, supporting its integration into standard treatment to enhance patients’ psychological well-being and quality of life.